2022
DOI: 10.2196/30791
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Acceptability of Wrist-Wearable Activity-Tracking Devices: Systematic Review of the Literature

Abstract: Background Numerous wrist-wearable devices to measure physical activity are currently available, but there is a need to unify the evidence on how they compare in terms of acceptability and accuracy. Objective The aim of this study is to perform a systematic review of the literature to assess the accuracy and acceptability (willingness to use the device for the task it is designed to support) of wrist-wearable activity trackers. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 72 publications
2
72
1
1
Order By: Relevance
“…Although moderate- to vigorous-intensity reliability and validity measures were not available for the Garmin Vivofit 4, Garmin wearables are found to be valid and reliable for measuring steps [ 27 ]. Coupled with the high acceptability [ 28 ] and affordability of the Garmin Vivofit 4, we found it to be a good fit for this study.…”
Section: Methodsmentioning
confidence: 65%
“…Although moderate- to vigorous-intensity reliability and validity measures were not available for the Garmin Vivofit 4, Garmin wearables are found to be valid and reliable for measuring steps [ 27 ]. Coupled with the high acceptability [ 28 ] and affordability of the Garmin Vivofit 4, we found it to be a good fit for this study.…”
Section: Methodsmentioning
confidence: 65%
“…Although numerous studies have shown that the accuracy of digital devices in measuring behavioral and physiological data may vary [77][78][79][80], most (20/31, 65%) of the included studies used different digital devices to synthesize qualitative or quantitative findings, which can be considered a gap in the literature on digital biomarkers; for example, the SR by Hannan et al [41] included various wearable digital devices (Garmin Forerunner, Fitbit Charge, My Wellness Key accelerometer, Yamax Digiwalker pedometer, Gex vital signs sensor, Nokia smartphone, and SenseWear Mini Armband) as interventions to quantitatively summarize the evidence for cardiac rehabilitation. By contrast, another study used only a Fitbit device to generate a meta-analysis for physical activity [46].…”
Section: Digital Devices Physiological and Behavioral Data And Sensorsmentioning
confidence: 99%
“…The loss in reliability compared with traditional ECG is minimal and can be neglected as long as heart disease is not the focus of the investigation. 4 7 …”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used metric is step counts 3. Reviews find an acceptable-to-high accuracy of step estimates across a variety of activity monitors,3 4 also for older adults 5. Not only are steps the least error-prone activity metric,4 they allow clear-cut recommendations for physical activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation